2016
DOI: 10.1136/neurintsurg-2015-012172
|View full text |Cite
|
Sign up to set email alerts
|

Primary acute stroke thrombectomy within 3 h for large artery occlusion (PAST3-LAO): a pilot study

Abstract: Our study demonstrates that primary SRT in AIS from LAO is safe and feasible and is associated with complete recanalization and good outcome. Further study is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Lodi et al reported that primary stent retriever thrombectomy within three hours without IV thrombolysis in acute ischemic stroke from larger vessel occlusion with a high NIHSS score (!10) is associated with efficient recanalization in all cases and good outcomes. 19 These findings showed that early initiation of endovascular therapy resulted in early recanalization, which might have been reflected in good functional outcome. 19 Three hours after stroke onset can be one of the important time indices in endovascular thrombectomy.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Lodi et al reported that primary stent retriever thrombectomy within three hours without IV thrombolysis in acute ischemic stroke from larger vessel occlusion with a high NIHSS score (!10) is associated with efficient recanalization in all cases and good outcomes. 19 These findings showed that early initiation of endovascular therapy resulted in early recanalization, which might have been reflected in good functional outcome. 19 Three hours after stroke onset can be one of the important time indices in endovascular thrombectomy.…”
Section: Discussionmentioning
confidence: 77%
“…19 These findings showed that early initiation of endovascular therapy resulted in early recanalization, which might have been reflected in good functional outcome. 19 Three hours after stroke onset can be one of the important time indices in endovascular thrombectomy. In-hospital workflow should be designed so as to deliver patients with ALVO with an OTP <3 h to the angiography suite for the start of treatment.…”
Section: Discussionmentioning
confidence: 77%
“…After reviewing the risk and benefit including cost and most current evidence, 26,27 patient wanted EVMT without thrombolytic. Additionally, author had a pilot trial 28 of primary EVMT without IV tPA that demonstrated similar results of the most recent RCT. 26,27 Patient was told that the chances of complete perfusion may be less if no tPA is chosen, but, there were no differences in outcomes.…”
Section: Review Of Literature Using Real Casesmentioning
confidence: 78%